PENGARUH RASIO LIKUIDITAS DAN SOLVABILITAS TERHADAP KINERJA KEUANGAN PERUSAHAAN - rahmi, namira ufrida; Simanjorang, Bella Rosa; Pasaribu, Ridoi Gilbert; fan, Yulis (Akuntansi Prima, 2024)
Financial performance is really needed by companies to determine the good and bad of the company's financial condition in a certain period. One way of measuring company performance is using financial ratio analysis. This research aims to examine the effect of liquidity ratios (CR) and Solvency (DER) on financial performance (ROA) in pharmaceutical companies for the 2021-2023 period, both partially and simultaneously. The samples were taken using purposive sampling technique. A sample of 14 companies was obtained from a total population of 15 companies. The sample was selected using a purposive sampling technique. The analysis technique used was descriptive statistics, multiple linear regression. , classical assumption test, hypothesis test (T test and F test) and coefficient of determination. Data processing using the SPSS 26 program. Partial test results show that solvency has a negative and significant effect on financial performance. Liquidity has a positive and significant effect on financial performance. Activities has no effect on financial performance. Meanwhile, simultaneous test results show that liquidity, solvency and activity together have an effect on financial performanc